The exploration of online academic help-seeking behavior of first-generation college students in developing countries: evidence from China - Yuying, Fan; Nkansah, Jacob Oppong (Frontiers in Education, 2024)
With the continuous expansion of higher education globally, the number of firstgeneration college students (FGCS) is also increasing, particularly in developing countries where FGCS account for more than half of all college students. This qualitative study explores the experience of Chinese FGCS in online academic help-seeking (OAHS) behavior through semi-structured interviews. The narratives from fifty-eight participants expand the understanding of how FGCS use the Internet to seek academic help when their family cultural capital is insufficient, and also present the role of family in this process. Three themes are found. First, FGCS prefer one-way help-seeking compared to interactive help-seeking. This situation is consistent with FGCS' choice in traditional contexts. Second, the Internet is used by FGCS most of the time to address specific issues without assisting them in academic self-growth effectively. Third, Thirdly, FGCS crave more spiritual support and encouragement from families. Based on the theories of cultural capital and cultural mismatch, the findings reveal the cultural mismatch and behavioral characteristics of OAHS in the Chinese context, giving implications for university practitioners to provide targeted assistance and training to FGCS.Based on Reviewer 2 suggestion, I deleted 1.1 part and integrated the definitions of items into paragraphs.